2019
DOI: 10.1177/1940082919854058
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution Modeling in Latin America: A 25-Year Retrospective Review

Abstract: Species distribution modeling (SDM) is a booming area of research that has had an exponential increase in use and development in recent years. We performed a search of scientific literature and found 5,533 documents published from 1993 to 2018 using SDM, representing a global network of 4,329 collaborating institutions from 155 countries, with Brazil and of Brasilia were the most productive. From this body of literature, the most frequently modeled taxonomic groups were Chordata and Insecta, and the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 93 publications
0
38
0
2
Order By: Relevance
“…Ecological niche models have often been used to model and project rodent distributions and niches, but a large proportion of these studies are restricted to species found in the Americas (Martínez-Salazar et al 2012;Bean et al 2014;Kubiak et al 2017;Flores-Zamarripa & Fernández 2018;Urbina-Cardona et al 2019;Pardi et al 2020). African rodents have also been studied using ENM techniques; Taylor et al (2015) showed that trends in the distribution of Afromontane rodents reflect changes in biomes predicted by past, present, and future climate scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological niche models have often been used to model and project rodent distributions and niches, but a large proportion of these studies are restricted to species found in the Americas (Martínez-Salazar et al 2012;Bean et al 2014;Kubiak et al 2017;Flores-Zamarripa & Fernández 2018;Urbina-Cardona et al 2019;Pardi et al 2020). African rodents have also been studied using ENM techniques; Taylor et al (2015) showed that trends in the distribution of Afromontane rodents reflect changes in biomes predicted by past, present, and future climate scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution modeling (SDM) is widely used to study biogeography, biodiversity patterns, evolutionary ecology, and to inform conservation efforts including reintroduction planning and predicting species' distribution shifts in response to climate change (Urbina-Cardona et al 2019). Overall, SDM explores and utilizes possible interactions between species occurrence records and environmental variables to calculate and produce a probability map of environmental suitability for a species in a given area.…”
Section: Introductionmentioning
confidence: 99%
“…SDM can help identify the potential distribution range of an endangered species that may be included in protected area planning (Thapa et al 2018), resolve taxonomy issues for species groups whose other traits may not be clearly distinguishable and conclusive (van Schingen et al 2016), predict vulnerable regions for invasive species risk (Ren et al 2016), determine areas of refugia that may be home to many rare and endemic species (Tang et al 2018), and examine processes influencing biodiversity and evolution over a long timescale (Musher et al 2020). The wide range of applications has pushed the development of many different SDMs approaches, among which Maximum Entropy (Maxent) is among the most commonly used (Urbina-Cardona et al 2019). Compared to other modeling approaches, Maxent only requires presence records, and still produces robust results when only a small number of occurrences is available (Elith et al 2006, Phillips et al 2006, Pearson et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…SDM has become a valuable tool for assessing habitat suitability and resource conservation to protect important plant species and to predict suitable cultivation regions . SDM is widely applied to analyze potential distribution of endangered species and to predict changes of species distributions under different climate change scenarios (Urbina-Cardona et al 2019). Species distribution modeling includes biophysical correlation model, climate element index method, generalized linear model (GLM), multivariate adaptive regression splines (MARS), genetic algorithm for rule-set production (GARP), maximum entropy (MaxEnt) and boosted regression trees (Sharma et al 2018).…”
Section: Introductionmentioning
confidence: 99%